PENGARUH BRAND AMBASSADOR DAN ADVERTISING CAMPAIGN TERHADAP MINAT BELI KONSUMEN PADA MARKETPLACE TOKOPEDIA - Tri Bawa Antara, I Komang; Ketut Warmika, I Gde (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.05.TAHUN.2024, 2024)
Buying interest is something related to the plan of prospective consumers to buy a product. Buying interest is very influential on a company to get customers. This study aims to analyze the influence of brand ambassadors and advertising campaigns on buying interest in the Tokopedia marketplace. The sample of this research is people who know the Tokopedia marketplace. This shelter is located in Denpasar City. The number of samples was determined by non-probability sampling method, namely purposive sampling, in order to obtain a total sample of 102 respondents. Data was collected through the distribution of questionnaires. The data analysis technique used is multiple linear regression analysis. The results of this study found that there is a positive and significant influence between brand ambassadors on consumer buying interest. In the Tokopedia marketplace, this means that the higher the brand ambassador, the higher consumer buying interest. There is a positive and significant influence between advertising campaigns on consumer buying interest in the Tokopedia marketplace. This means that the higher the advertising campaign level, the higher consumer buying interest.